The doctrine of God ; part 2 - Barth, Karl, 1886-1968; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland T and T Clark, 1957)
Includes indexes.
Original German ed. : Die Kirchliche Dogmatik, II : Die Lehre von Gott, 2
Keywords: God, characteristics of